The Role of Muslimah as Agents of Change in the Middle of a Morality Emergency: Study of Takhrij and Syarah Hadith - Ilmi, Husna Dhiyaul; Asy-Syahidah, Qorina Himmati (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the hadith about shalihah women. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about pious women in the history of Muslim No. 1467. The results and discussion of this study indicate that the status of the hadith is of hasan quality, in which this hadith is the same as the authentic hadith, that is, it can be used as evidence. This study concludes that the hadith narrated by Muslim No. 1467. is relevant to be used as a motivation for women to always look after izzah and iffah to make themselves included in the group of pious women amid a morality emergency.